A Comparison Differences in Students’ Perceptions Toward Using Teacher’s Feedback - Syahputra, Andi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to compare their perceptions between gender and their age toward using the teachers’ feedback in their classroom. This study applied a quantitative method with survey method, which allowed the data to be quantified and analyzed using statistical analysis. In collecting the data, the Questionnaire Feedback, Identification, School Trajectories that measure their perceptions about Effective Teachers’ Feedback (EFT) and Ineffective Teachers’ Feedback (IEFT) have been used. The samples are 125 students, who are 53 boys and 72 girls, also 17 and 18 years old. The data are analyzed by descriptive statistics. The findings showed that there were statistically significant differences perceptions among students across their genders (p≤0.001) on EFT perceived. Furthermore, there is a significant difference between 17 years old students and 18 years old students (p≥0.05) on EFT perceived. As the result, the students’ gender and their age have main effect, with girls perceiving are more effective than boys, which leads them to report receiving more feedback from their teachers when compared to boys, and 18 years old students’ percept more than 17 years old students on teachers’ feedback toward their reading achievement.